2018
DOI: 10.5152/tjg.2018.17415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemodialysis combined with hemoperfusion on severe acute pancreatitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Previous studies have found that CVVH combined with HP can clear various inflammatory mediators more effectively than CVVH alone [21]. Li et al [22] also suggested that CVVH combined with HP could better remove toxic metabolites and inflammatory mediators in SAP than HP alone, and it not only shortens the time of symptoms disappearing but also decreases the incidence of complications and the mortality. Based on clinical experience and previous studies, PIRRT combined with HP (PIRRT + HP) is theoretically more effective in treating AP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that CVVH combined with HP can clear various inflammatory mediators more effectively than CVVH alone [21]. Li et al [22] also suggested that CVVH combined with HP could better remove toxic metabolites and inflammatory mediators in SAP than HP alone, and it not only shortens the time of symptoms disappearing but also decreases the incidence of complications and the mortality. Based on clinical experience and previous studies, PIRRT combined with HP (PIRRT + HP) is theoretically more effective in treating AP.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of β2-MG and metabolic disorder of uremic patients may produce a large amount of PTH, which is involved in the occurrence and development of renal diseases (29,30). Cr and BUN belong to small molecular toxins and are one of the important factors causing uremic symptoms and complications (7,31,32). Inflammation is a vital factor that causes the occurrence or aggravation of various diseases, and is also crucial in the pathogenesis of complications in uremic patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis can remove blood urea nitrogen (BUN), creatinine (Cr) and bilirubin. In addition, it is mainly effective in removing internal wastes and adjusting acid-base balance through the principle of semipermeable membrane dialysis (7). Hemoperfusion can adsorb inflammatory mediators, such as interleukin (IL)-1, IL-6, IL-8, tumor necrosis factor-α and prothrombin-activating factor, to reduce inflammatory reaction (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, HP targets molecules that tend to be more difficult to remove with conventional HD or with continuous RRTs (CRRT) and has the capacity to remove molecules with MW up to 30,000 Da depending on the characteristics of the sorbent material [ 31 ]. When combined with HD/CRRT, the sorbent can be placed before or after the dialyzer and enhance the removal of middle molecules that are not sufficiently removed by HD, such as B2M [ 32 ].…”
Section: Technical Aspects Of Hemoperfusionmentioning
confidence: 99%